استخدام وسائل الأغنية العربية لترقية مهارة الاستماع لطلاب الفصل السابع بمدرسة منبع العلوم جوريت المتوسطة الإسلامية فرانجاسيلا لومبوك الشرقية - Riadhi, Moh; Rauhillah, Siti; Suryawati, Suryawati (Lughatu Ad-dhat, 2024)
ABSTRACT    Istima' skills are a person's ability to digest or understand words or sentences uttered by certain interlocutors or media. The researcher found several problems in learning Arabic, such as students being less active in the learning process, and even students were sleepy and bored learning Arabic. So that it is necessary to use interesting learning media such as the Aarab song media so that students are enthusiastic about learning, quickly understand lessons, so that students' listening skills can increase. The aims of this reseach were: (1) to find out the use of Arabic songs in learning Arabic for MTs Mamba'ul Ulum Jurit students, (2) to find out how effective the use of song media is in improving istima' skills for MTs Mamba'ul Ulum Jurit students. The research method used is the experimental method and the control class. while the methods used in data collection are observation, tests, interviews. The results of this reseach are: the effectiveness of using song media in improving students' istima' skills is known from the results of the T-test which shows that the result of the T-count is 7,061 while the T-table with dk (n1 + n2 – 2 = 25 + 25 - 2 = 48), then ttable = 1,772. Based on the results of the analysis, the price of tcount > ttable is obtained7,061> 1,722 This shows that in testing the hypothesis Ha is accepted and HO is rejected. Thus the alternative hypothesis (Ha) which reads: "The use of song media has a positive and significant effect on improving Arabic listening skills in Mts. Mamba'ul Ulum Jurit this is effective. Keywords: Arabic Song Media, Listening Skills